The Implementation of Semester Learning Plan (RPS) on MaharahIstima’ Course by Using Cartoon Story Maker - Aulia Mustika Ilmiani; Hamidah Hamidah; Nurul Wahdah; Mahfuz Rizqi Mubarak (IAIN Salatiga, 2020)
This is a descriptive qualitative research which aims to describe the implementation of Semester Learning Plan (RPS) on MaharahIstima’ Course by Using Cartoon Story Maker and its distinct characteristics from the previous RPS. The subject of this research is the Arabic language lecturers of IAIN Palangka Raya who teach MaharahIstima’ course. It uses observations, interviews, and documentations for the data collection techniques, and is validated using triangulation method. The results showed that there were nine learning activities of the implementation of Cartoon Story Maker based semester learning plan, namely; (1) Providing information to the students about the course’s learning objectives. (2) Giving apperception about the learning material. (3) Preparing and displaying Cartoon Story Maker media. (4) Students listen and prepare their stationeries (5) Students mention the main and supporting ideas. (6) Providing responses and corrections (7) Reminding the students to write the new vocabulary obtained. (8) Students make conclusions (9) Providing an explanation or summary about the material. The specification of this RPS with the previous one is that it is designed and clearly described the assessment indicators which include a series of more innovative activities, where learning is more centred on students and lecturers only act as facilitators and monitor the learning objectives. Lecturers only provide learning resources by creating Cartoon Story Maker as an interesting and effective learning media.